Gasification of coal, Chenopodium Album biomass, and co-gasification of a coal-biomass mixture by thermogravimetric-gas analysis - Marco Antonio Ardila-Barragán, Ph. D. (c); Carlos Francisco Valdés-Rentería, Ph. D.; Brennan Pecha, Ph. D.; Alfonso López-Díaz, Ph. D.; Eduardo Gil-Lancheros, M.Sc.; Marley Cecilia Vanegas-Chamorro, Ph. D.; Jesús Emilio Camporredondo-Saucedo, Ph. D.; Luis Fernando Lozano-Gómez, M.Sc. (Revista Facultad de Ingeniería, 2019)
Gasification studies were performed on sub-bituminous coal of the province Centro in Boyacá state of Colombia, vegetable biomass Chenopodium album (cenizo) and co-gasification of coal-biomass mixtures agglomerated with paraffin in a thermogravimetric analyzer. Biomass synergistically promoted thermochemical transformation of the coal was observed. Experimental results were compared to equilibrium composition simulations. Ash fusibility tests of the coal-biomass mixture were carried out, which allowed to clarify its behavior, such as dry or fluid ash according to own chemical composition, during the gasification process. The experimental tests allowed determining the differences in thermal decomposition, between coal, cenizo and coal-biomass blend, which are attributable to the physicochemical properties of each one solid fuel. During the tests, gas chromatography analyses were performed to establish the compositions of the syngas. The syngas obtained from biomass had the highest concentration of CO and the lowest H2; the coal and the coal-biomass mixture were slightly minor respectively. Concentrations of CH4, CO2 and C2H4 were similar between coal and biomass. This result is consistent with the higher calorific value of the coal syngas. The production of syngas from the coal-biomass mixture had the lowest contents of H2 and CO due to synergistic phenomena that occur with the fuel mixture. The co-gasification of the mixture gave the highest syngas production, carbon conversion, and thermal efficiency. These results indicate the viability of co-gasification of coal-Chenopodium album agglomerated mixtures. In gasification of non-agglomerated mixtures of coal-cenizo, the biomass can be burned directly without producing syngas.